Virtues in German Proverbs - มีวงศ์อุโฆษ ชูศรี (Journal of Letters, 2018)
The research aims to study and ascertain essential virtues found in common German proverbs and to analyse the main factors which have caused or affected these virtues. The “Encyclopedia of German proverbs” of Karl Friedrich Wilhelm Wander, which contains more than 250,000 proverbs, has been used as the primary source for this purpose. The paper describes 25 essential virtues, which have been found in the proverbs, as well as hints at three major factors that have always maintained such an important effect on those virtues. These three major factors are the Christian doctrine, the patriarchal system of the German society in former times, and finally, the German monarchy.